Short-Term Efficacy of Pulsed Radiofrequency Thermal Stimulation on Acupoints for Chronic Low Back Pain: A Preliminary Study of a Randomized, Single-Blinded, Placebo-Controlled Trial. (12th August 2018) - Ku, Boncho; Jun, Minho; Lee, Jun-Hwan; Jeon, Young-Ju; Kim, Young-Min; Kang, Jaehui; Lee, Yu-Jung; Kim, Kahye; Heo, Hyun; Kim, Jaeuk U.
Abstract : Background. The objective of this study was to evaluate the pain-relief efficacy of thermal stimulation induced by a pulsed radiofrequency (PRF) thermal stimulation applied to acupoints (APs) in patients with low back pain (LBP). The study was designed as a randomized, single-blinded, placebo-controlled trial . Methods. Fifty-six LBP patients whose minimum pain intensity score on a visual analogue scale (VAS, 0-100 mm) was more than 30 mm were randomly allocated to either the placebo-controlled or the treatment group at a 1:1 ratio. The treatment and placebo-controlled groups received PRF thermal stimulation plus cupping therapy and cupping therapy only, respectively. Each patient was scheduled to receive a total of three treatment sessions over one week with allowing a window up to 4 days. Six of the 13 predefined APs were selected differently for each session depending on the change in patient's symptoms and intensity of pain. The primary outcome was the mean difference between the placebo-controlled and treatment group of VAS changes from the baseline to the end of the follow-up period. Results. The patients' reported VAS scores from baseline to the end of follow-up (average: 9.8 days) were significantly decreased by 8.036 points (two-sided 95% CI, -11.841 to -4.231) and 13.393 points (two-sided 95% CI: 17.198 to -9.588) in the treatment and the placebo-controlled groups, respectively. However, the change in VAS scores between the treatment group and the placebo-controlled group was not significantly different (2.015 mm, two-sided 95% CI: -5.288 to 9.317). Conclusion. The trial results indicated that treatment with either PRF thermal stimulation with cupping therapy or cupping therapy alone effectively relieved LBP. The efficacy of PRF thermal stimulation combined with cupping therapy was not superior to that of cupping therapy alone. Trial registration number: Clinical Research Information Service (KCT0002137 ). The trial was registered retrospectively on 10 November, 2016.